2000
DOI: 10.1073/pnas.230438497
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative subunit interactions within the oligomeric envelope glycoprotein of HIV-1: Functional complementation of specific defects in gp120 and gp41

Abstract: The envelope glycoprotein (Env) of HIV-1 is displayed on the surface of the virion or infected cell as an oligomer of multiple gp120͞gp41 complexes. We sought to unravel the relationships between this oligomeric structure and the requirements for sequential interactions with CD4 and coreceptor (CCR5 or CXCR4). We used a quantitative cell fusion assay to examine the effects of coexpressing pairs of Envs, each nonfunctional because of a specific defect in one of the essential properties. We observed efficient fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 40 publications
4
68
1
Order By: Relevance
“…The existence of complementation by itself argues that trimers do not need to have two wild-type monomers to function, since complementing Envs have either only one wild-type SU or only one wild-type TM. Yang et al found no complementation in their system, but this contrasts with the results reported here as well as several other reports (32,35,47,48). Previous reports on complementation do not distinguish whether one or both heterotrimers are functional.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The existence of complementation by itself argues that trimers do not need to have two wild-type monomers to function, since complementing Envs have either only one wild-type SU or only one wild-type TM. Yang et al found no complementation in their system, but this contrasts with the results reported here as well as several other reports (32,35,47,48). Previous reports on complementation do not distinguish whether one or both heterotrimers are functional.…”
Section: Discussioncontrasting
confidence: 99%
“…The mechanism of complementation is not yet clear, though it is usually considered in terms of SU and TM from different monomers being able to work together to induce fusion (32,35,47,48). Our results support another mechanism that may contribute to complementation in some cases, namely, heterotrimerization increasing steady-state levels and transport to the plasma membrane of mutant Env species that misfold as homotrimers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous analyses of subunit complementation (i.e., generation of functional mixed trimers upon coexpression of two Envs with different inactivating mutations) used the Env-mediated cell fusion assay (14,15), which is highly sensitive for detecting Env function. Here we wished to apply the Env pseudotype virion infection system to test for complementation with virus particles.…”
Section: Demonstration Of Env Complementation With Hiv Virion Particlesmentioning
confidence: 99%
“…We devised a functional strategy based on a previously described Env complementation system (14,15) to distinguish between cis versus trans mechanisms of epitope masking. The results are discussed in terms of various proposed trimer models based on structural analyses and molecular modeling.…”
mentioning
confidence: 99%